EFEKTIVITAS AIR REBUSAN JAHE TERHADAP INTENSITAS NYERI HAID PADA MAHASISWI UNIVERSITAS TRIATMA MULYA: EFEKTIVITAS AIR REBUSAN JAHE TERHADAP INTENSITAS NYERI HAID PADA MAHASISWI UNIVERSITAS TRIATMA MULYA - Hutabarat, Naomi Christina; Kesumawati, Ketut Anom Sri (WELL BEING, 2021)
Menstrual pain is pain that is felt in the lower abdomen when menstruating without any abnormalities in the reproductive organs, it can occur before or during menstruation. Pain during menstruation can be reduced, one way is the management of non-pharmacological therapy by giving herbal drinks in the form of ginger boiled water. Ginger contains essential oils in which there is a chemical content of gingerol which has a strong effect on inhibiting prostaglandin biosynthesis where excessive prostaglandin formation can cause excessive uterine contractions so that it can also increase pain. The purpose of this study was to determine the effect of giving ginger boiled water on the intensity of menstrual pain in students at Triatma Mulya University, Jembrana. Research Methods: The type of research used is a variation of the study in the form of a quasi-experimental plus the concept of one-group pretest-posttest. A total of 135 students of Triatma Mulya Jembrana University were the population in this study. Samples were taken by doing purposive sampling then obtained specimens of twenty (20) female students. description of the information formulated with paired t-test. When water has not been given from boiling ginger, the intensity of menstrual pain shows a range between five to eight which has an average result of seven then after giving water from boiling ginger on the 2nd day shows a range between one to four which has an average of 2.55. the conclusion of the t-test experiment shows that the number at t as much as 24.106 in df 19 has a relevant level of (p) 0.000. Ginger boiled water has the potential to relieve menstrual pain. Triatma Mulya University students who experience pain during menstruation, can use ginger boiled water as an alternative treatment for menstrual pain. Future researchers can conduct further research on the benefits of ginger on menstrual pain by simplifying the serving or by turning ginger into a product